Knowledge and Prevalence of Sexual Grooming in Academia: Basis for Awareness Campaign - Evangelista Marjorie S; Casta Riza Joy M; Yranela Hazelyn M.; Delos Santos Herock; Bernal Hernando Jr. L. (Randwick International of Education and Linguistics Science Journal, 2024)
This research aims to illuminate sexual grooming in academic settings, underscoring the imperative for awareness and preventive measures. The study is theoretically grounded in Ward and Sieger's Pathways Model, incorporating Finkelhor’s Precondition Model, Marshall and Barbaree’s Integrated Theory, and Hall and Hirschman’s Quadripartite Model. This comprehensive framework provides a nuanced understanding of the psychological mechanisms at play in sexual grooming. To address gaps in educators' awareness, the study utilizes random sampling to assess 25 teachers from senior high and tertiary levels. A survey instrument, featuring closed and Likert scale questions, gauges respondents' knowledge of sexual grooming definitions, signs, and prevalence in academia. Aligned with the UNICEF report on child sexual violence, the study underscores the urgency of tackling such issues. The conceptual framework employs the input-process-output model, considering teachers' profiles, survey responses, and potential implications for an awareness campaign. The methodology incorporates a structured online questionnaire covering demographic information, knowledge assessment, training awareness, reporting procedures, and the perceived importance of addressing sexual grooming. By exploring educators' comprehension and experiences regarding sexual grooming, this research strives to contribute to a safer learning environment. The findings will inform targeted training programs and bolster child protection measures within educational institutions. As dedicated proponents of the Department of Education's mission, the study endeavors to bridge the awareness gap and foster child-friendly, secure, and motivating academic environments.